A Study on Mental Health of Healthcare Workers during Covid-19 - M.K Navya (PT FORMOSA CENDEKIA GLOBAL, 2022)
The spread of corona virus (COVID-19) across the globe and the associated morbidity and mortality challenged the nations by several means. One such under recognized and unaddressed area is the mental health issues medical staff develops during the pandemic.so I want to know /study the mental health of health care workers during COVID-19. This has been going since 2020 of March because of that workers are exposed to so much of stress levels. This study is conducted to find out whether all the above till now have had any impact on the mental health of workers in terms of health care workers are not. The study is about mental health of health care workers during covid-19. The study help to analyse whether there is increase the level of stress, mood swings, well-being, sleeping habits, emotional support, confidence, eating habits, energy levels, ability to concentrate, fatigue, appetite, emotional exhaustion, disturbances in sleep due to Covid 19.